The Anthropocene as an Event, not an Epoch. (9th March 2022) - Gibbard, Philip; Walker, Michael; Bauer, Andrew; Edgeworth, Matthew; Edwards, Lucy; Ellis, Erle; Finney, Stanley; Gill, Jacquelyn L.; Maslin, Mark; Merritts, Dorothy; Ruddiman, William
ABSTRACT: Over the course of the last decade the concept of the Anthropocene has become widely established within and beyond the geoscientific literature but its boundaries remain undefined. Formal definition of the Anthropocene as a chronostratigraphical series and geochronological epoch following the Holocene, at a fixed horizon and with a precise global start date, has been proposed, but fails to account for the diachronic nature of human impacts on global environmental systems during the late Quaternary. By contrast, defining the Anthropocene as an ongoing geological event more closely reflects the reality of both historical and ongoing human–environment interactions, encapsulating spatial and temporal heterogeneity, as well as diverse social and environmental processes that characterize anthropogenic global changes. Thus, an Anthropocene Event incorporates a substantially wider range of anthropogenic environmental and cultural effects, while at the same time applying more readily in different academic contexts than would be the case with a rigidly defined Anthropocene Series/Epoch.